In-situ Functionalization of Metal Electrodes for Advanced Asymmetric Supercapacitors - Sun, Leimeng; Wang, Xinghui; Wang, Yurong; Xiao, Dongyang; Cai, Weifan; Jing, Yuan; Wang, Yanrong; Hu, Fangjing; Zhang, Qing (Frontiers in Chemistry, 2019)
Nanostructured metal-based compound electrodes with excellent electrochemical activity and electrical conductivity are promising for high-performance energy storage applications. In this paper, we report an asymmetric supercapacitor based on Ti and Cu coated vertical-aligned carbon nanotube electrodes on carbon cloth. The active material is achieved by in-situ functionalization using a high-temperature annealing process. Scanning and transmission electron microscopy and Raman spectroscopy confirm the detailed nanostructures and composition of the electrodes. The TiC@VCC and CuxS@VCC electrodes show a high specific capacity of 200.89 F g-1 and 228.37 F g-1, respectively, and quasi-rectangular shapes at different scan speeds, demonstrating good capacitive characteristics. The excellent performance can be attributed to a large surface area to volume ratio and high electrical conductivity of the electrodes. Furthermore, an asymmetric supercapacitor is assembled with TiC@VCC as anode and CuxS@VCC as cathode. The full device can operate within the 0-1.4 V range, and shows a maximum energy density of 9.12 Wh kg-1 at a power density of 46.88 W kg-1. These findings suggest that the metal-based asymmetric electrodes have a great potential for supercapacitor applications.